FAKTOR-FAKTOR YANG MEMPENGARUHI KEMAUAN PENGUSAHA UMKM UNTUK MEMBAYAR PAJAK DI KANTOR PELAYANAN PAJAK PRATAMA SEMARANG TENGAH I - Shofiyah, 11.05.52.0086; Badjuri, Achmad (Students Journal of Accounting and Banking, 2016)
This study aimed to examine the effect of the tax paying consciousness, knowledge and understanding of the tax laws, good perception on the effectiveness of the tax system, taxpayer attitude, quality of service, tax penalties, the level of confidence in the goverment and legal system of the willingness to pay taxes.Population in this study is the individual taxpayers who do business in the region Kantor Pelayanan Pajak Pratama Semarang Tengah 1 by 1.4662.Â Sampling is done using methods Purposive Sampling and the total sample of 108 respondents. Primary data collection method used is the questionnaire. And data analysis using multiple linear regression method. Research shows that consciousness of paying tax, knowledge and understanding of the tax laws, good perception on the effectiveness of the tax system, taxpayer attitude, quality of service, tax penalties, the level of confidence in the goverment and legal system significant positive effect on willingness to pay taxes. Â Keywords:Â Consciousness of Paying Taxes, Knowledge and Understanding of The Tax Laws, Good Perception on The Effectiveness of The Tax System, Taxpayer Attitude, Quality of Service, Tax Penalties, The Level of Confidence In The Goverment and Legal System and Willingness to Pay Taxes